Multiwavelength Brillouin-Raman fiber laser utilizing linear and ring cavity structures: A comparative study - Abass A.K.; Al-Mansoori M.H.; Jamaludin M.Z.; Abdullah F.; Al-Mashhadani T.F.; Ali M.H. (2023)
Two tunable multiwavelength Brillouin-Raman fiber lasers in the long-band region utilizing both linear and ring cavities were com pared. The effect of Raman pump power on the performance parameters of the two cavities was investigated. At 10 dBm Brillouin pump power, up to 41 single spacing channels were obtained in the linear cavity, compared with only six double spacing Stokes signals in the ring cavity. Tuning ranges reached 27 and 49 nm at the optimum Raman pump powers of 325 and 400 mW for the linear and ring laser cavities, respectively. The ring cavity exhibited better Stokes power fluctuation of 0.491 dB compared with the 1.045 dB fluctuation in the linear cavity. 2013 IEEE.